Assessment of the requisites of microbiology based infectious disease training under the pressure of consultation needs - Erdem Hakan; Tekin-Koruk Suda; Koruk Ibrahim; Tozlu-Keten Derya; Ulu-Kılıc Aysegul; Oncul Oral; Guner Rahmet; Birengel Serhat; Mert Gurkan; Nayman-Alpat Saygin; Eren-Tulek Necla; Demirdal Tuna; et al. (BMC, 2011)
Abstract Background Training of infectious disease (ID) specialists is structured on classical clinical microbiology training in Turkey and ID specialists work as clinical microbiologists at the same time. Hence, this study aimed to determine the clinical skills and knowledge required by clinical microbiologists. Methods A cross-sectional study was carried out between June 1, 2010 and September 15, 2010 in 32 ID departments in Turkey. Only patients hospitalized and followed up in the ID departments between January-June 2010 who required consultation with other disciplines were included. Results A total of 605 patients undergoing 1343 consultations were included, with pulmonology, neurology, cardiology, gastroenterology, nephrology, dermatology, haematology, and endocrinology being the most frequent consultation specialties. The consultation patterns were quite similar and were not affected by either the nature of infections or the critical clinical status of ID patients. Conclusions The results of our study show that certain internal medicine subdisciplines such as pulmonology, neurology and dermatology appear to be the principal clinical requisites in the training of ID specialists, rather than internal medicine as a whole.